The Influence of Institutional Ownership and Audit Quality on The Quality of Financial Reporting Mediated by Internal Control - Azi, Reza Satrio; Akbar, Taufik (LifeSciFi, 2025)
The increasing importance of financial transparency in manufacturing firms highlights the need to understand the factors influencing financial reporting quality. This study investigates the effects of institutional ownership and audit quality on financial reporting quality, with internal control as an intervening variable. The research population consists of 50 manufacturing companies listed on the Indonesia Stock Exchange (BEI) from 2021 to 2024. Purposive sampling was employed to select the sample, and secondary data were collected from the BEI website. Data analysis was conducted using Eviews 12 software. The results reveal that institutional ownership significantly impacts internal control, audit quality also influences internal control, institutional ownership affects financial reporting quality, audit quality does not significantly impact financial reporting quality, internal control positively affects financial reporting quality; institutional ownership does not influence financial reporting quality through internal control, indicating partial mediation; and audit quality does not affect financial reporting quality through internal control, demonstrating complete mediation.